2016
DOI: 10.1039/c5sm03072b
|View full text |Cite
|
Sign up to set email alerts
|

Linking micellar structures to hydrogelation for salt-triggered dipeptide gelators

Abstract: Some functionalised dipeptides can form hydrogels when salts are added to solutions at high pH. We have used surface tension, conductivity, rheology, optical, confocal and scanning electron microscopy, (1)H NMR and UV-Vis spectroscopy measurements to characterise fully the phase behaviour of solutions of one specific gelator, 2NapFF, at 25 °C at pH 10.5. We show that this specific naphthalene-dipeptide undergoes structural transformations as the concentration is increased, initially forming spherical micelles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
110
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 71 publications
(121 citation statements)
references
References 57 publications
11
110
0
Order By: Relevance
“…Small‐angle neutron scattering (SANS) data was also collected (Supporting Information, Figure S6 and Table S2). In agreement with our previous work,9 the data before heating is best fit to a hollow cylinder with a radius of 36.9±0.1 Å and a core radius of 19.1±0.2 Å. After a heat/cool cycle, the radius decreases to 31.2±0.1 Å (in line with the SAXS data) and the core radius also decreases to 9.2±0.3 Å.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…Small‐angle neutron scattering (SANS) data was also collected (Supporting Information, Figure S6 and Table S2). In agreement with our previous work,9 the data before heating is best fit to a hollow cylinder with a radius of 36.9±0.1 Å and a core radius of 19.1±0.2 Å. After a heat/cool cycle, the radius decreases to 31.2±0.1 Å (in line with the SAXS data) and the core radius also decreases to 9.2±0.3 Å.…”
supporting
confidence: 91%
“…The concentration range coincides with our previous work on the phase diagram for 2NapFF, where we showed that worm‐like micelles are formed above around 1 mg mL −1 , with a significant increase in the viscosity above 5 mg mL −1 9. Hence, this heat‐induced behavior requires that specific aggregates exist at room temperature, rather than this being a heat‐induced structural transition.…”
supporting
confidence: 90%
See 3 more Smart Citations